Social background effects in the transition to a doctoral degree – Empirical evidence from a German prospective study. (October 2018) - Bachsleitner, Anna; Becker, Michael; Neumann, Marko; Maaz, Kai
Highlights: We examine the effect of social background on the transition to doctoral studies. The educational background influences the probability to start a doctoral degree. Nearly half of the effect can be explained by differences in performance. Highly relevant factors are also field of subject and type of tertiary institution. Abstract: This study examines the relationship between social background and the transition to a doctoral degree, based on data from a longitudinal study ( N  = 2214) conducted in Germany. Drawing on theoretical concepts developed by Boudon (1974) and Erikson and Jonsson (1996), the study investigates what proportion of the social background effect is transmitted via performance differences (primary effect) and the degree to which mechanisms of a cost-benefit analysis (secondary effect) and educational biographical factors can contribute to the explanation. Tertiary graduates from more highly educated family backgrounds are found to have a higher probability of transitioning to a doctoral programme, especially if they have at least one parent who holds a doctoral degree. The effect decomposition shows that nearly half of the social background effect can be attributed to differences in final secondary school and university marks and to performance on standardised tests. On closer examination, the social background effect can mainly be traced back to differences in final marks and in the choice of subject and type of tertiary institution.